Numerical study of steady pipe flows and head loss coefficients - Bangun, Emma Patricia; Mahdi, Nabil (Universitas Negeri Semarang, 2024)
The study concerns steady pipe flows within 90o-bend and T-junctions, the head loss coefficients and the physical mechanisms responsible for the energy loss. Numerical viscous flow modelling based on SimpleFOAM solver were implemented in the study. Although secondary flow acts as the mechanism of energy loss in both the bend and in the branch flow of T-junction, the head loss coefficient in the former more critically depends on Reynolds (Re) number. This is supported by the comparison of the streamline fields and the radially varying profiles of the pressures from both cases. The location of flow separation prior to the secondary flow in the bend changes with Re number unlike the fixed location at the junction in the branch flow. The study confirms a practical implication related to the dependence of the head loss coefficients for pipe with 90o-bend and T-junction on flow velocity in an analysis of pipe network.